Invasive pneumococcal disease among hospitalized children in Brazil before and after the introduction of a pneumococcal conjugate vaccine. Issue 7 (11th February 2020) - Berezin, Eitan Naaman; Jarovsky, Daniel; Cardoso, Maria Regina Alves; Mantese, Orlando Cesar
Abstract: Background: Most of the available data on invasive pneumococcal disease in Latin America are derived from laboratory-based surveillance systems. There is a lack of epidemiological data on the disease severity and mortality from hospitalized patients with pneumococcal infection. Methods: In this hospital-based retrospective historical series of hospitalized children with laboratory-confirmed IPD, we evaluated changes in disease episodes, in-hospital fatality rates, and need for intensive care unit admission after the inclusion of PCV10 in the Brazilian vaccination schedule. Invasive pneumococcal strains isolated by culture were serotyped. Changes over time were assessed, and pre-vaccination (2005–2009) to post-vaccination (2011–2015) disease rates and serotypes were compared. Results: 260 patients with IPD and positive pneumococcal isolates were identified (198 during the pre-PCV10 period). When comparing both periods, hospitalizations were reduced from 20 cases to 5 cases per 10, 000 pediatric admissions (p < 0.0001). Likewise, fatalities reduced from 6.6 to 2.0 cases per 10, 000 pediatric admissions (p < 0.0001). Pneumonia was the most frequent clinical diagnosis (58%) – of which 49.6% had pleural effusion – followed by meningitis (22%) and bacteremia (15.9%). Overall 30% of cases were sent to ICU, with no percentual changes after PCV10. Additional PCV13 serotypes increased from 7% before vaccine introduction to 21% after PCV10 use. Similarly, serotypes not included in PCV13 increased from 11% to 29%. Conclusions: There was a significant reduction in the hospitalizations rates, ICU admissions, and fatalities due to IPD after PCV10 introduction in Brazil. Cases due to PCV10 serotypes were reduced, while infections rates caused by non-PCV10 serotypes increased.